Think Piece: Pioneers as Relational Subjects? Probing Relationality as Phenomenon Shaping Collective Learning and Change Agency Formation - Heila Lotz Sisitka (Environmental Association of Southern Africa, 2018)
This paper deliberates on how relationality is framed in collective learning and change agency formation processes, with an emphasis on green economy and renewable energy learning contexts. The paper is not focused on empirical analysis of relationality in collective learning, but rather probes the phenomenon in order to provide more carefully constituted theoretical and analytical tools for further empirical research. The paper uses references to South African and Danish cases (albeit in slightly different ways), and, through this, it sets out to provide tools for generative insights and research into a recent international policy and strategy process which is bringing national-level Green Economy Learning Assessments (GELA) into being, including one in South Africa. Central to these GELAs is the notion of participatory or relational competence, which appears to be a central feature of collective learning, although this is not empirically analysed in this paper. In case study work undertaken for the GELA in South Africa that focused on South Africa's major renewable energy development, and in the Samsø Island renewable energy transition case in Denmark, this competence appeared to come into focus in praxis. Interestingly, however, it appeared to come into focus colloquially as a discourse on 'pioneers' or 'champions', a phenomenon noticed in both the South African and Danish contexts. This paper probes this phenomenon further, especially since it initially appears to be contradictory to the emphasis on participatory and relational competence in the GELA study framework. This is because the concept of 'pioneer/champion' appears to highlight individual capabilities rather than collective, relational competences. Yet, on closer inspection, it is indeed the relational competences of the pioneer/champion, who is constituted as a 'relational subject' with a key role to play in producing shared relational goods, that appears to be significant to the collective learning and action process. This, as argued in the paper, requires a differentiation of relationism and relational realism. This Think Piece, which thinks with both theory and praxis, therefore offers a possible framework for more detailed empirical studies on relationality in collective learning and change agency formation.